Short Communication: Antimicrobial properties in cloacal fluid of olive ridley sea turtle (Lepidochelys olivacea) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Praja RN, Yudhana A, Haditanojo W, Oktaviana V. 2021. Short Communication: Antimicrobial properties in cloacal fluid of olive ridley sea turtle (Lepidochelys olivacea). Biodiversitas 22: 3671-3676. There were several speculations regarding the main purpose of sea turtle cloacal fluid, such as lubrication during egg deposition, which could help reduce egg speed as they are dropped in nesting sand, or contain antimicrobial properties to protect their eggs from pathogenic microorganisms. However, the exact purpose of this fluid which is mucous-like in consistency remains unknown. This study aimed to identify antimicrobial properties in the cloacal fluid of olive ridley sea turtles. Cloacal fluid samples were collected during nesting season in Banyuwangi City coastal areas, East Java Province, Indonesia. Moreover, the Kirby-Bauer diffusion disk method recorded antimicrobial properties and tested against several bacterial colonies collected from sand in natural nesting chambers. This preliminary study also concluded that antimicrobial properties were recorded when presented against several bacteria colonies from natural nesting sands namely Escherichia coli, Salmonella spp., and Bacillus spp. Furthermore, the present study should be expanded to include other bacteria and fungi colonies. In addition, results from the present study could be used to develop methods in creating antibiotics similar to those found naturally in natural nesting areas to prevent microorganism contamination and globally increase hatchling success, which has a greater impact to support sea turtle conservation efforts as endangered species.
Keywords: Antimicrobial properties, Biodiversity, Cloacal fluid, Olive ridley.